Penerapan Prinsip Ekonomi Islam dalam Meningkatkan Pertumbuhan Ekonomi Negara Berkembang di Asia - Ata Rosyidah Karimah; Anisa Dian Kholida; Muhammad Saiful Fajar; Melisa Dwi Laelatul Kusna; Amalia Nuril Hidayati (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This research discusses the application of Islamic economic principles in enhancing economic growth in developing countries. Developing countries often face issues of economic inequality, poverty, and unemployment, which can be addressed through an economic approach based on moral values and social justice. The theory used in this research includes maqasid al-shariah, which emphasizes social welfare, as well as Islamic economic principles that prohibit riba, gharar, and maysir, and implement profit-sharing systems in financing. Additionally, this research examines the role of zakat and waqf as instruments of wealth redistribution that can reduce social inequality. The research method used is qualitative with a library study approach, collecting and analyzing relevant literature to support the understanding of the application of Islamic economic principles. The findings indicate that the application of Islamic economic principles can create more inclusive and sustainable economic growth, improve societal welfare, and reduce socio-economic inequality in developing countries. Sharia financial concepts, such as mudharabah and musyarakah-based financing, also provide fairer access to financing for small and medium-sized enterprises. Overall, Islamic economics offers an effective alternative in addressing various economic challenges in developing countries.